2009
DOI: 10.1016/j.jenvp.2008.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Where to take a study break on the college campus: An attention restoration theory perspective

Abstract: College students spend much of their time on campus engaged in activities that require sustained directed attention, which may lead to attention fatigue. They would benefit from campus settings that provide effective restoration breaks and allow them to return to their work cognitively refreshed. Studies have found direct exposure to nature, viewing nature through windows, and viewing images of nature are restorative. In the present study, college students, instructed to imagine themselves cognitively fatigued… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
161
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 238 publications
(200 citation statements)
references
References 22 publications
7
161
0
9
Order By: Relevance
“…It is similar with the findings of Felsten (2009), who demonstrated exposure to restorativeness characteristics of simulated nature in indoor campus settings has recovery effects. This study found that experience of restorativeness in campus outdoor open spaces has positive effect on students psychological restoration.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It is similar with the findings of Felsten (2009), who demonstrated exposure to restorativeness characteristics of simulated nature in indoor campus settings has recovery effects. This study found that experience of restorativeness in campus outdoor open spaces has positive effect on students psychological restoration.…”
Section: Discussionsupporting
confidence: 89%
“…Campus open spaces, which are rich in providing of soft fascination experiences and supporting students required activities or behaviors highly lead to restoration experience. Similar finding with less experience of extent has been addressed in Felsten (2009), where campus indoor settings with no views of nature did not induce great mental restoration. Campus outdoor open spaces, however, is suggested to be ideal setting in experience of restoration by engaging to abundance restorative objects (Lau et al 2014;Seitz et al 2014).…”
Section: Discussionsupporting
confidence: 84%
“…Mental fatigue typically occurs when an individual works and/or concentrates for extended periods of time (Kaplan & Kaplan, 1989;Liprini, 2014). Studies conducted by Felsten (2009) and Kjellgren & Burkhall (2010) measured the attention restoration of students exposed to green spaces. The researchers found that not only were green spaces conducive to restoring attention, but the students using them tended to be more relaxed and displayed increased levels of energy (Felsten, 2009;Kjellgren & Burkhall, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the natural environment uniformly had the highest perceived restorativeness rating (Herzog et al, 1997). Felsten (2009), however, contended that both real and non-real natural settings (such as murals of natural settings) would have a restorative effect on students who were cognitively depleted after classes. The results did not fully support his notions and indicated that dramatic nature scenes had a greater restorative effect than mundane real and non-real nature settings (Felsten, 2009).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation